Hydration status, sweating rate, heart rate and perceived exertion after running sessions in different relative humidity conditions: a randomized controlled trial - Nascimento, Matheus A. Do [UNESP] (2020)
The purpose of this study was to analyze the impact of running in normal relative humidity (RH = 53%) and very high RH (94%) on hydration status (HS), sweating rate (SR), heart rate (HR), and rating of perceived exertion (RPE). Fourteen men (25.2 ± 6.6 yrs) performed two sessions of treadmill running. Body mass (normal RH: -1.35%, very high RH: -1.65%) HS (normal RH: -14.8%; very high RH: -20.8%) were reduced while RPE (normal RH: +26%; very high RH: +28%) and HR were increased (very high RH: +5.8%: 20-40 min, +3.1%: 40-60 min, +3%: 20-40 min; +2.3%: 40-60 min for normal RH). As expected, SR was significantly greater during very high RH (-20/8%) compared to normal RH (-14.8%). Running in very high RH at moderate temperature has a greater negative impact on SR, HS, body mass, HR, RPE in men than running in normal RH at the same temperature, which places the runner in greater danger of heat illnesses such as heat exhaustion or heat stroke.